Coffea arabica seedlings genotypes are tolerant to high induced selenium stress: Evidence from physiological plant responses and antioxidative performance - Mateus, Matheus Pereira de Brito [UNESP] (2020)
Selenium (Se) is considered a beneficial element to higher plants based on its regulation of antioxidative system under abiotic or biotic stresses. However, the limit of beneficial and toxic physiological effects of Se is very narrow. In the present study, the antioxidant performance, nutritional composition, long-distance transport of Se, photosynthetic pigments, and growth of Coffea arabica genotypes in response to Se concentration in solution were evaluated. Five Coffea arabica genotypes (Obatã, IPR99, IAC125, IPR100 and Catucaí) were used, which were grown in the absence and presence of Se (0 and 1.0 mmol L−1) in nutrient solution. The application of 1 mmol L−1 Se promoted root browning in all genotypes. There were no visual symptoms of leaf toxicity, but there was a reduction in the concentration of phosphorus and sulfur in the shoots of plants exposed to high Se concentration. Except for genotype Obatã, the coffee seedlings presented strategies for regulating Se uptake by reducing long-distance transport of Se from roots to shoots. The concentrations of total chlorophyll, total pheophytin, and carotenoids were negatively affected in genotypes Obatã, IPR99, and IAC125 upon exposure to Se at 1 mmol L−1. H2O2 production was reduced in genotypes IPR99, IPR100, and IAC125 upon exposure to Se, resulting in lower activity of superoxide dismutase (SOD), and catalase (CAT). These results suggest that antioxidant metabolism was effective in regulating oxidative stress in plants treated with Se. The increase in sucrose, and decrease in SOD, CAT and ascorbate peroxidase (APX) activities, as well as Se compartmentalization in the roots, were the main biochemical and physiological modulatory effects of coffee seedlings under stress conditions due to excess of Se.